2015
DOI: 10.3390/rs70506026
|View full text |Cite
|
Sign up to set email alerts
|

MODIS EVI and LST Temporal Response for Discrimination of Tropical Land Covers

Abstract: MODIS enhanced vegetation index (EVI) and land surface temperature (LST) are key indicators for monitoring vegetation cover changes in broad ecosystems. However, there has been little evaluation of these indices for detecting changes in a range of land covers in tropical regions. In this study, we investigated the characteristics and seasonal responses of LST and EVI for four different land covers in Lao tropical forests: native forest, rubber plantation, mixed wooded/cleared areas and agriculture. We calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…5 have not yet been considered in this study. In addition, the enhanced vegetation index (EVI) was more sensitive than NDVI in some regions, such as tropical rainforests with high biomass [83]. The saturation of NDVI might underestimate the correlation between LST and vegetation cover.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…5 have not yet been considered in this study. In addition, the enhanced vegetation index (EVI) was more sensitive than NDVI in some regions, such as tropical rainforests with high biomass [83]. The saturation of NDVI might underestimate the correlation between LST and vegetation cover.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…where G is the gain factor, NIR is the Near Infra-red band, C1 and C2 are the coefficients of the aerosol resistance term, and L is the canopy background. Whilst the Normalized Difference Vegetation Index (NDVI) [49] is commonly used [22,45], as in a number of other forest studies, we chose the EVI, [50][51][52] due to its improved performance in areas of high biomass as a result of a de-coupling of canopy background signals and a reduction in atmospheric influences [53]. We used the MODIS EVI product MOD13Q1 at 250 m spatial and a 16-day temporal resolution downloaded from the United States Geological Survey (USGS; Table 1).…”
Section: Modis Evimentioning
confidence: 99%
“…For decades, the use of satellite-derived data for estimating LST has been well reported in the literature (Jimenez-Munoz, Sobrino 2003, Zhang et al 2006, Xiao et al 2007, David 2008, Nwilo et al 2012, Oguz 2013, Zaharaddeen et al 2016, Jeevalakshmi et al 2017, Deng et al 2018, Tarawally et al 2018. It has also been suggested that the inclusion of LST can improve land cover and vegetation monitoring (Mildrexler et al 2007, Sobrino, Julien 2013, Phompila et al 2015. Also, change in land cover is an important indicator that affects LST.…”
Section: Introductionmentioning
confidence: 99%